2014
DOI: 10.1021/bm500174p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyglutamide-Based Metal-Chelating Polymers and Their Site-Specific Conjugation to Trastuzumab for Auger Electron Radioimmunotherapy

Abstract: Three types of metal-chelating polymers (MCPs) with hydrazide end groups were synthesized. (1) The first set of polymers (the F-series) was synthesized with a furan end group, and all of the pendant groups along the chain carried only a diethylenetriaminepentaacetic acid (DTPA) metal-chelating functionality. The hydrazide was introduced via a Diels-Alder reaction between the furan and 3,3'-N-[ε-maleimidocaproic acid] hydrazide (EMCH). (2) The P-series polymers was designed to carry several copies of a nuclear-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 36 publications
(71 reference statements)
2
50
0
Order By: Relevance
“…The mPEG-PBLG- t Boc polymers were then treated with an excess of ethylenediamine (EDA) at room temperature (RT) to convert the benzyl groups to aminoethylamide pendant groups. 44 This reaction was carried out for different times ranging from 3 to 5 h to optimize both the amine conversion and preservation of the t Boc end group. By comparing the integration of the t Boc protons at 1.44 ppm to that of the signal at 4.34 ppm (backbone methine), the surviving t Boc functionality for mPEG-PGlu(EDA) 18 -Boc in this step stayed the same for the reaction times of 3 h ( 1 H NMR spectrum not shown) and 5 h ( Figure S8 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mPEG-PBLG- t Boc polymers were then treated with an excess of ethylenediamine (EDA) at room temperature (RT) to convert the benzyl groups to aminoethylamide pendant groups. 44 This reaction was carried out for different times ranging from 3 to 5 h to optimize both the amine conversion and preservation of the t Boc end group. By comparing the integration of the t Boc protons at 1.44 ppm to that of the signal at 4.34 ppm (backbone methine), the surviving t Boc functionality for mPEG-PGlu(EDA) 18 -Boc in this step stayed the same for the reaction times of 3 h ( 1 H NMR spectrum not shown) and 5 h ( Figure S8 ).…”
Section: Resultsmentioning
confidence: 99%
“…The authors found that the resulting site-specifically Tc-99m-labeled radioimmunoconjugate proved more stable than an analogous, traditionally conjugated variant. More recently, in an effort to develop In-111-labeled immunoconjugates for Auger electron radiotherapy, Lu et al site-specifically conjugated polymers bearing ~30 DTPA each to trastuzumab via oxidation with NaIO 4 , reaction with the hydrazide-bearing polymers, and reduction with NaBH 3 CN [ 86 ]. The resulting constructs were shown to have approximately 1.2 polymers/mAb and could be successfully labeled with 111 In in high yield and at higher specific activities than traditional, lysine-conjugated trastuzumab-DTPA.…”
Section: Glycansmentioning
confidence: 99%
“…Considering that NaIO 4 could oxidize the carbohydrate portion of SPG-1, 35 these findings may indicate that the carbohydrate portion of SPG-1 is the major immune active site. Therefore, NaIO 4 oxidation remarkably decreased the T cell immune response of SPG-1.…”
Section: Effect Of Naio 4 Treatment On Spg-1 T Cell Immune Responsementioning
confidence: 94%